Prospects for Mangrove Reforestation Using the Silvofishery Method in Aquaculture Areas in Bireuen Regency, Aceh - Rima Shah Putra; Ernawita; Iswahyudi (Jurnal Akuakultur Indonesia, 2025)
The conflict between shrimp productivity and mangrove conservation should not occur. One of the solutions is the "silvofishery" pond method, which integrates both through the intercropping of mangroves and shrimp, particularly for traditional pond farmers who are the most aquaculture practitioners in Indonesia. Unfortunately, silvofishery is not yet widespread. Therefore, this research is proposed to map the understanding and acceptance of pond farmers in Bireuen Regency towards mangroves and their intercropping with shrimp and identify the barriers and challenges farmers face in its future implementation. The research was conducted in three sub-districts, Kuala, Peusangan, and Jangka, using in-depth interviews with ten farmer respondents selected through the snowball method. Quantitative interview data were analyzed using basic statistics, while qualitative data were analyzed using the interactive model approach of Miles and Huberman. The research findings indicate that mangrove reforestation in Bireuen Regency is still threatened by conversion back to other uses by farmers. Meanwhile, silvofishery remains challenging due to at least three issues: (1) latent issues such as the per capita land area shrinking, making it increasingly difficult for farmers to allocate land for mangrove planting in ponds; (2) not all farmers readily accept the explanation of silvofishery, that's why it needs to be initiated and proven first by the government, and (3) there must be the anticipation for the return of bird and crab pests to the ponds due to the attraction of mangroves. Overall, the prospect of mangrove reforestation using the silvofishery method at the farmer level in Bireuen Regency is still low. Therefore, earnest efforts are needed to change farmers' paradigms towards mangroves and solve current aquaculture problems.